2020
DOI: 10.2334/josnusd.20-0083
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses to pediatric stainless steel crowns

Abstract: A systematic review was conducted to identify the biological responses, allergic reaction, hypersensitivity, toxicity, and ion release profile associated with pediatric stainless steel crowns (SSCs) in the existing literature. A systematic search was undertaken according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. The inclusion criteria consisted of patients younger than 20 years of age with SSC placement on primary or permanent teeth and in vivo and in vitro exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Studies have evaluated the performance of stainless steel crowns in comparison to other restoration methods and found that stainless steel crowns showed a higher lifespan and durability [ 15 , 16 , 17 , 18 ]. The stainless steel crowns have reasonable costs and are less technique sensitive during placement [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have evaluated the performance of stainless steel crowns in comparison to other restoration methods and found that stainless steel crowns showed a higher lifespan and durability [ 15 , 16 , 17 , 18 ]. The stainless steel crowns have reasonable costs and are less technique sensitive during placement [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the degree of corrosion that metal undergoes, its carcinogenesis ability varies. The symptoms can appear at distance from metal alloy [173][174][175].…”
Section: Materials Saftymentioning
confidence: 99%
“…In addition, the more SSC appeared, the more nickel ions were released. Based on this research, the release of nickel ions was not influenced by how much nickel ion content was in the SSC but rather by the level of resistance of SSC to electrochemical corrosion by saliva [17,[22][23][24][25]. The research was also conducted to see the nickel lysis of the trimming process when adjusting the stainless-steel crown.…”
Section: Disadvantage Of Stainless-steel Crown (Ssc)mentioning
confidence: 99%
“…If these impacts arise, they will require countermeasures. Therefore, this literature review would discuss studies related to SSC materials and their contents as well as hypersensitivity reactions that can be caused by a metal content in SSC and actions that must be taken before and after restoration considering that SSC will be in the oral cavity for a long time, about 8-9 years until the permanent replacement tooth erupts [15].…”
Section: Introductionmentioning
confidence: 99%